Ignacio M. Sánchez Prado, editor. Pierre Bourdieu in Hispanic Literature and Culture. Palgrave MacMillan, 2018. - Katie J. Vater (Studies in 20th & 21st Century Literature, 2019)
Review of Sánchez Prado, Ignacio M., editor. Pierre Bourdieu in Hispanic Literature and Culture. Palgrave MacMillan, 2018.
Keywords: Bourdieu; sociology of literature; Hispanic Studies